E-governance diffusion: Population level e-service adoption rates and usage patterns. (March 2019) - Solvak, Mihkel; Unt, Taavi; Rozgonjuk, Dmitri; Võrk, Andres; Veskimäe, Märten; Vassil, Kristjan
Highlights: Adoption and diffusion of e-governance among the population of Estonia were studied. Appx 2.1 billion rows of behavioral logs from 2003 to 2015 were analyzed. Results suggest that e-governance adoption is linear, not sigmoid-shape. Adoption rate grows faster and peak adoption rate increases as user age decreases. E-governance usage depth and duration increased with age, though not linearly. Abstract: This paper investigates how e-governance diffuses in population. Specifically, the cumulative and peak adoption rates of e-governance, the usage patterns of duration (number of days services were used) and depth (number of services used) of usage were analyzed. The data comprised 2.1 billion rows of anonymized service call log data of the entire Estonian e-governance ecosystem, the X-Road, from 2003 to 2015. The results showed that e-governance diffusion was linear, not sigmoid-shape, as literature suggests. In general, cumulative adoption rate grows faster and peak adoption rate increases as user age decreases, and is higher among women. E-service usage duration does not increase faster than usage depth. Usage depth and duration increased with age, though not linearly, and were higher in women. This is the first study to use the behavioral data logs of the entire population across more than 10 years to study technology diffusion on the example of e-governance. The results complement the contemporary technology adoption and diffusion theories, and this study could be of practical relevance to other nations implementing their own e-services for governance.